Political Islam and Religious Violence in Post-New Order Indonesia - Mudhoffir, Abdil Mughis (Masyarakat: Jurnal Sosiologi, 2015)
This paper tries to understand why religious violence increasingly occurs in post-New Order Indonesia. There are two dominant views in understanding this. First, the secu- rity approach that perceives the violence as a result of the emergent of “radical” agent of political Islam in the more open political space. In this regard, the state is considered weak because the iron hand as used by the authoritarian regime in the past New Order has disappeared. Thus, the strong security instruments are needed as a solution, such as the law on anti-terrorism and the police force of anti-terrorism (Densus 88). Second, the cultural approach views violence as caused by the inability of society to build the religious tolerance. Society is considered weak. Religious expression in the political arena is believed as the source of the emergent of intolerant acts. To conquer this, intensive inter-religious dialogues are required. The author argues that those two approaches are not adequate. The historical fact shows that the emergence of political Islam today is the result of the oscillated relationship between Islam and the authoritarian state during the New Order period. In addition, the Indonesian historical experience also clearly illustrates that the presence of political Islam is nothing but a form of response to the critical social-political- economic situation. Political Islam does not appear in a vacuum, but it emerges from the crisis where another populist response from the left is absent.